Regulating Content on Social Media Copyright, Terms of Service and Technological Features - Tan, Corinne (UCL Press, 2018)
How are users influenced by social media platforms when they generate content, and does this influence affect users' compliance with copyright laws? These are pressing questions in today's internet age, and Regulating Content on Social Media answers them by analysing how the behaviours of social media users are regulated from a copyright perspective. Corinne Tan, an internet governance specialist, compares copyright laws on selected social media platforms, namely Facebook, Pinterest, YouTube, Twitter and Wikipedia, with other regulatory factors such as the terms of service and the technological features of each platform. This comparison enables her to explore how each platform affects the role copyright laws play in securing compliance from their users. Through a case study detailing the content generative activities undertaken by a hypothetical user named Jane Doe, as well as drawing from empirical studies, the book argues that - in spite of copyright's purported regulation of certain behaviours - users are 'nudged' by the social media platforms themselves to behave in ways that may be inconsistent with copyright laws.